Effectiveness Of Applicatison Of Online Objection Submission Service (E-Objection) At The Primary Tax Office Of South Bekasi - Ratih Kumala; Agus Subagyo; Dwikora Harjo; Pebriana Arimbhi; Mainita Hidayati (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Along with advances in information and communication technology, the conventional service system has shifted to an electronic-based service system. This encourages the Directorate General of Taxes to take part in carrying out reforms, one of which is by simplifying the online filing procedure for submitting objection letters (e-objection), which has only been running as of August 1, 2020. This study was conducted to see the effectiveness of the application of online objection letter submission services (e-objection) in improving service performance, obstacles that arise and the efforts made by the Primary Tax Office of South Bekasi in improving the service performance of the e-objection feature. This research is a descriptive research with a qualitative approach. Data was collected through observation, interviews and documentation. The results of this study indicate that the e-objection feature has been successfully implemented at the Primary Tax Office of South Bekasi but few people use it. The reason is that the submission of the objection is unpredictable because it is not an obligation. These results are based on problem identification, program success, target success, satisfaction with the program and overall goal achievement on Campbell's theory in regarding criteria for measuring effectiveness. The obstacles faced by the Primary Tax Office of South Bekasi include the lack of campaign and the low quantity and quality of human resources in IT. Therefore, the efforts that need to be made by the Primary Tax Office of South Bekasi are conducting more frequent campaign and increasing the quantity and quality of human resources in IT.